CD226+ B cells in primary Sjögren’s syndrome: a key player in clinical manifestations and disease pathogenesis - Zhao, Ping; Song, Saizhe; Zhang, Song; Peng, Cheng; Cheng, Wei; Chang, Xin; Xie, Changhao; Hu, Zhongli; Liu, Cuiping (Frontiers in Immunology, 2025)
IntroductionPrimary Sjögren’s syndrome (pSS) is a systemic autoimmune disorder characterized by lymphocytic infiltration of exocrine glands, leading to sicca symptoms and systemic complications. CD226, a co-stimulatory receptor implicated in the pathogenesis of multiple autoimmune diseases including systemic lupus erythematosus (SLE), rheumatoid arthritis(RA), and pSS, regulates immune cell activation. However, the specific role of CD226+ B cells in pSS pathogenesis remains unclear. This study aims to elucidate the functional contribution of CD226+ B cells to pSS development and their clinical relevance.MethodsThe percentages of CD226 on T cells, B cells, CD56+ NK cells and CD14+ monocytes in the peripheral blood(PB) of pSS patients and healthy controls (HCs) were detected by flow cytometry.Multicolor flow cytometry was employed to examine the distribution of CD226 in B cell subsets of pSS patients, as well as the expression levels of co-stimulatory molecules, activation and proliferation markers, immunoglobulins, and pro-inflammatory cytokines on both CD226+ B cells and CD226- B cells. Multicolor immunofluorescence staining was applied to detect the co-expression of B cells and CD226 in the salivary gland of pSS patients.Microarray analysis was conducted to analyze the transcriptomic profiles of sorted CD226+ CD19+ B cells and CD226- CD19+ B cells.ResultsCD226 expression in the peripheral blood of pSS patients was significantly increased on T cells, CD19+ B cells and CD14+ monocytes, but significantly decreased on CD56+ NK cells.We identified a distinct CD226+CD19+ B cell subset that exhibited pathogenic features in pSS. CD226 was significantly upregulated on B cells in the peripheral blood and salivary glands of pSS patients.CD226+ CD19+ B cell showed a stronger correlation with clinical features, disease activity, and prognosis in pSS patients.The ROC curve demonstrated that CD226+ CD19+ B cell exhibited significant diagnostic capability to distinguish pSS patients from healthy controls and to differentiate disease activity.This subset also exhibited heightened activation and pro-inflammatory phenotypes.DiscussionCD226+ B cells are expanded in pSS, strongly correlating with clinical manifestations and disease activity. These cells display enhanced effector profiles (activation, cytokine/immunoglobulin production) and demonstrate diagnostic utility. Our findings identify CD226+ B cell as a pathogenic driver in pSS, positioning CD226 as a promising novel therapeutic target and biomarker.